PERSONAL ORIENTATION OF PREPARATION OF THE FUTURE TEACHERS IN CONDITIONS OF CONTINUOUS FORMATION(EDUCATION) AND INTEGRATION INTO THE INTERNATIONAL EDUCATIONAL SYSTEM (Pedagogy of Higher and Secondary Education, 2007)
New paradigm of education is expressed in tendency to its «humanization», humanizing of educational sphere, changing of student’s position from an object to a subject of a training process. The problem of quality education, promoted by Bologna Declaration, can't be successfully solved without the transition of the system of continuous educational-discipline training to personal-oriented pedagogical process in Higher School. The article deals with the conditions of transforming social-professional experience into a personal plan of activity.
Keywords: Bologna Declaration; education; social-professional experience